DEVELOPMENT OF CORPORATE GOVERNANCE IN COMMERCIAL BANKS (Academicia Globe: Inderscience Research, 2021)
This article discusses the necessary organizational system to improve the system of corporate governance in commercial banks and control over their achievement, as well as the issues of improving the efficiency of the system of corporate governance in the period of socio-economic reforms carried out in our country and improving the corporate governance of the Joint-Stock Companies on the basis